World Economy Spring 2021: Recovery stays on track - Klaus-Jürgen Gern; Philipp Hauber; Stefan Kooths; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2021)
The global economy continued to recover in the winter semester, despite the number of new infections with the coronavirus rising sharply and containment measures tightened again in many countries. Industrial production and world trade have already fully catched up with activity levels before the pandemic and appear to be little affected by the second wave of Covid-19. While the European economy did slip into recession again, the decline in GDP is not expected to be dramatic and should be followed by a strong recovery from spring onward, provided that progress in vaccination allows a substantial and sustained relaxation of measures designed to suppress the virus. In the course of this year, the global upturn will thus increasingly extend to economic sectors that remain severely impeded for the time being, such as tourism and entertainment, and to economies that are particularly geared to these activities. On a purchasing power parity basis, global output is expected to increase by 6.7 percent in 2021 and by 4.7 percent in 2022, thus progressively closing the gap to the pre-crisis path of activity towards the end of the forecast period. We have raised our December forecast by 0.6 percent for both this year and next, with a particularly strong improvement in the outlook for the United States. World trade in goods is expected to grow by 7.5 percent this year. With growth of 4.7 percent this year and next, respectively, Towards the end of the forecast horizon world trade will thus be even higher than expected before the crisis.
Keywords: 330; USA; Emerging Markets & Developing Countries; Europe; advanced economies; emerging economies; monetary policy; Americas; Asia; Business Cycle World; China